How Sustainability Cues on Product Pages Shape Consumer Behavior - Masopustová, Kateřina; Houdek, Petr, 1981-; Urbanová, Klára; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis examines whether sustainability-related cues displayed on product pages influence consumer behavior in an online grocery context. Building on behavioral economics, digital choice architecture, and the SHIFT framework, the study tests social proof, value-aligned, and prosocial/local sustainability messages. A two-stage empirical design was used, consisting of a pre-test to validate message clarity and credibility, followed by a controlled online survey experiment simulating an e-commerce environment. Responses were measured using willingness to pay and add-to-cart decisions for real grocery products. While the pre-test revealed perceptual differences between message types, the main experiment found no statistically significant effects of sustainability cues on shifting behavior. Product category and individual sustainability orientation were stronger drivers of consumer decisions.
Vedoucí práce: Petr Houdek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses